2000
DOI: 10.1139/l00-038
|View full text |Cite
|
Sign up to set email alerts
|

Suspended sediment concentration and deformation of riverbed in a frazil jammed reach

Abstract: The presence of ice in rivers affects hydrodynamic conditions through changes in both the river's boundary conditions and its thermal regime. Therefore, the characteristics of sediment transport and the deformation of the river channel in ice-covered rivers are quite different from those experiencing conventional open channel flow. The variables of ice behavior, ice jamming extent, sediment transport, and deformation of the riverbed during ice periods are interrelated on the basis of both physical arguments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 5 publications
1
24
0
1
Order By: Relevance
“…This section examines sediment transport and riverbed deformation in the Hequ Reach of the Yellow River in China, as outlined by Sui et al (2000Sui et al ( , 2006. The Hequ Reach of the Yellow River is approximately 700 kilometres in length and has a broad and shallow morphology.…”
Section: Riverbed Deformation Under Ice Jam Conditions 41 Hequ Reachmentioning
confidence: 99%
See 2 more Smart Citations
“…This section examines sediment transport and riverbed deformation in the Hequ Reach of the Yellow River in China, as outlined by Sui et al (2000Sui et al ( , 2006. The Hequ Reach of the Yellow River is approximately 700 kilometres in length and has a broad and shallow morphology.…”
Section: Riverbed Deformation Under Ice Jam Conditions 41 Hequ Reachmentioning
confidence: 99%
“…The largest recorded sediment concentration in frazil ice in the Hequ Reach was 25 kilograms per metre cubed of ice; this is a much larger sediment concentration than what has been recorded in water flowing under the ice (7 kilograms per cubic metre of water). During an ice jam event from December 1986 to March 1987 Sui et al (2000) examined riverbed deformation at a cross section in the Hequ Reach. As shown in Figure 6, over the period of approximately 3 months, the river width expanded and sediment scour expanded the deepest parts of the river channel.…”
Section: Riverbed Deformation Under Ice Jam Conditions 41 Hequ Reachmentioning
confidence: 99%
See 1 more Smart Citation
“…Starosolszky (1970) and Sui et al (2000) suggested that the theory of bed load movement could be borrowed to describe the movement of ice under ice cover. Atkinson and Waters (1978) used Meyer-Peter formula to describe the movement of ice particles.…”
Section: Computational Domain For Body-fitted Coordinate Systemmentioning
confidence: 99%
“…An ice cover alters the hydraulics of an open channel by imposing an extra boundary to the flow, altering the water level and flow velocity compared to the ice free case . Ice alters the flow regime, incipient motion of bed material and the transport of sediment by temporarily storing water through ice jams and results in differences in riverbed deformation as compared to that observed under open flow conditions Sui et al, 2000;. Under specific conditions such as continuous incoming of frazil ice from upstream due to low temperature, ice jam may be formed.…”
Section: Introductionmentioning
confidence: 99%